XVIII-XX АСРЛАРДА ҚОРАҚАЛПОҚЛАРДА МЕТАЛЛСОЗЛИК ҲУНАРМАНДЧИЛИГИ - Турганов, Б.Қ. (SCIENCE and SOCIETY, 2019)
The article deals with the history of the development of such handicraft of Karakalpak people as metal processing in the XVIII-XIX centuries. There were one or two blacksmiths in each Karakalpak village at that period. Blacksmiths and craftsmen, began conducting their activities in Kungrad, Chimbai and Khodjeily in the XIX century. The raw-material for blacksmiths were delivered from Russia and Bukhara emirate. Karakalpak blacksmiths produced tools for agriculture, household items and horse bards.